Age and Gender Confound PROMIS Scores in Spine Patients With Back and Neck Pain. Issue 3 (April 2021) - Jevotovsky, David S.; Tishelman, Jared C.; Stekas, Nicholas; Moses, Michael J.; Karia, Raj J.; Ayres, Ethan W.; Fischer, Charla R.; Buckland, Aaron J.; Errico, Thomas J.; Protopsaltis, Themistocles S.
Study Design: This was a single-center retrospective review. Objectives: To explore how age and gender affect PROMIS scores compared with traditional health-related quality of life (HRQL) in spine patients. Methods: Patients presenting with a primary complaint of back pain (BP) or neck pain (NP) were included. Legacy HRQLs were Oswestry Disability Index (ODI), Neck Disability Index (NDI), and Visual Analogue Scale (VAS). PROMIS Physical Function (PF), Pain Intensity (Int), and Pain Interference (Inf) were also administered to patients in a clinical setting. Patients were grouped by chief complaint, age (18-44, 45-64, 65+ years) and gender. Two parallel analyses were conducted to identify the effects of age and gender on patient-reported outcomes. Age groups were compared after propensity-score matching by VAS-pain and gender. Separately, genders were compared after propensity-score matching by age and VAS-pain. Results: A total of 484 BP and 128 NP patients were matched into gender cohorts (n = 201 in each BP group, 46 in each NP group). Among BP patients, female patients demonstrated worse disability by ODI (44.15 vs 38.45, P = .005); PROMIS-PF did not differ by gender. Among NP patients, neither legacy HRQLs nor PROMIS differed by gender when controlling for NP and age. BP and NP patients were matched into age cohorts (n = 135 in each BP group and n = 14 in each BP group). Among BP patients, ANOVA revealed differences between groups when controlling for BP and gender: ODI ( P < .001), PROMIS-PF ( P = .018), PROMIS-Int ( P < .001) PROMIS-Inf ( P < .001). Among NP patients, matched age groups differed significantly in terms of NDI ( P = .032) and PROMIS-PF ( P = .022) but not PROMIS-Int or PROMIS-Inf. Conclusions: Age and gender confound traditional HRQLs as well as PROMIS domains. However, PROMIS offers age and gender-specific scores, which traditional HRQLs lack.